ADVERSE DRUG REACTION - Mariyono, Harbanu H; Suryana, Ketut (journal of internal medicine; Vol. 9, No. 2 Mei 2008, 2012)
There are lots of new drugs that made for therapy, prevent and even as a diagnostic tools. Beside the desired effect there were also undesired effect that can occur when managing patient with drugs which then we call adverse drugs reaction. An adverse reaction to a drug has been defined as any noxious or unintended reaction to a drug that is administered in standard doses by the proper route for the purpose of prophylaxis, diagnosis, or treatment. Adverse drug reaction can be devided in two groups, which is reactions than can occur on everyone and the ones that can only occur on susceptible ones. One of the adverse drug reaction is drug allergy. History taking is the most important thing on diagnosing drug allergy, one that can help was Naranjos score. We can run few more test to defined the type of Adverse Drug Reaction. For managing patient with adverse drug reaction, we have to avoid drugs that induce the reaction, premedication and also desensitisation.
Keywords: adverse drug reaction, drug allergy, diagnosis, treatment